Uji Aktivitas Antibakteri Ekstrak Etanol Daun Bugenvil (Bougainvillea glabra) pada Bakteri Staphylococcus aureus - Legistari, Mirna; Ramandha, Muhammad Eka Putra; Pratiwi, Baiq Yulia Hasni (Biocity Journal of Pharmacy Bioscience and Clinical Community, 2024)
Bougainvillea leaves contain various secondary metabolite compounds, such as flavonoids, tannins, and saponins. These compounds have the potential to be antibacterial to treat infectious diseases caused by the pathogenic bacteria Staphylococcus aureus. This study aims to determine the antibacterial activity of bougainvillea leaf ethanol extract against the growth of S. aureus bacteria. This study carried out antibacterial activity tests using the agar well-diffusion method. Data analysis used the One-way ANOVA statistical test, with the Shapiro-Wilk normality test and the Levene homogeneity test. The results of phytochemical tests showed that the ethanol extract of bougainvillea leaves contains flavonoids, tannins, and saponins. In antibacterial tests with concentrations of 25%, 50%, 75%, and 100%, the diameter of the inhibition zone obtained ranged from 20-27.3 cm. This inhibition zone is included in the strong to very strong category. In addition, statistical tests showed that each concentration of bougainvillea leaf ethanol extract affected the growth of S. aureus bacteria compared to negative controls. Based on the description above, bougainvillea leaf ethanol extract has the potential to inhibit the growth of S. aureus.